Use of the Prostate Core Mitomic Test in Repeated Biopsy Decision-Making: Real-World Assessment of Clinical Utility in a Multicenter Patient Population. - Legisi, Lorena; DeSa, Elise; Qureshi, M. Nasar (American Health & Drug Benefits, 2016)
BACKGROUND: Prostate cancer is the most common cancer diagnosed in men in developed countries. Using molecular testing may help to improve outcomes in this clinically challenging group. Since 2011, the Prostate Core Mitomic Test (PCMT), which quantifies a 3.4-kb mitochondrial DNA deletion strongly associated with prostate cancer, has been used by more than 50 urology practices accessing pathology services through our laboratory in New Jersey. However, the use of a molecular test can only be beneficial if it affects patient management and improves outcomes. OBJECTIVE: To determine whether repeated biopsy decision-making was affected in a quantifiable manner through the adjunct use of molecular testing with the PCMT. METHODS: In this observational study we conducted 2 independent, structured query language database queries of our patient records at our laboratory, QDx Pathology Services, in Cranford, NJ. Query 1 included all men who had a negative prostate biopsy and a negative PCMT between February 1, 2011, and June 30, 2013. Men with a previous diagnosis of cancer were excluded. Query 2 included all men who had a negative prostate biopsy and a repeated biopsy between February 1, 2011, and September 30, 2013. The data exported for each query included the unique specimen number for an index biopsy, the interval between biopsies where present, the unique specimen number for a follow-up biopsy where present, histopathology for all biopsies, the biopsy procedure dates, the patient's date of birth, and the PCMT result when utilized. The patient rebiopsy rates and intervals were compared between the patients who were using PCMT and those who were not to assess whether the adjunct use of the PCMT impacted the rebiopsy decision-making process. RESULTS: Query 1 identified 644 men who had a negative biopsy and a negative PCMT result within the study period. Query 2 identified 823 men with a repeat biopsy after the initial negative index biopsy within the study period. Of these men, 132 had PCMT to inform their care. This patient population of 1467 men originated from US-based clinical urology practices. Evaluation of the impact on physician behavior demonstrated a general trend toward the earlier detection of prostate cancer on repeat biopsy by an average of 2.5 months and a coincident increase in cancer detection rates for urologists using the deletion assay in their rebiopsy decision-making process. Importantly, this trend was only observed when men with atypical small acinar proliferation (ASAP) on index biopsy were not considered. In the 644 men with a negative PCMT result, only 35 (5.4%) were subjected to a follow-up biopsy, with 5 (14.3%) of the 35 men identified as having cancer. Finally, the cohort of 132 men who had PCMT and repeat biopsy was compared with the published data supporting PCMT's ability to predict rebiopsy outcome. The key metrics of sensitivity and negative predictive value were comparable and within the 95% confidence intervals of the reported work. CONCLUSION: Molecular tests, such as the PCMT, are useful in addressing the sampling error of prostate needle biopsy and providing additional evidence to inform the clinical uncertainty regarding initial negative prostate biopsy when ASAP is not present. Longitudinal monitoring of clinical impact indicators provides the necessary inputs to better allocation of healthcare resources in the short- and long-term.